Non-invasive and fully two-dimensional quantitative visualization of transparent flow fields enabled by photonic spin-decoupled metasurfaces - Qingbin Fan; Peicheng Lin; Le Tan; Chunyu Huang; Feng Yan; Yanqing Lu; Ting Xu (Light: Science & Applications)
Abstract Transparent flow field visualization techniques play a critical role in engineering and scientific applications. They provide a clear and intuitive means to understand fluid dynamics and its complex phenomena, such as laminar flow, turbulence, and vortices. However, achieving fully two-dimensional quantitative visualization of transparent flow fields under non-invasive conditions remains a significant challenge. Here, we present an approach for achieving flow field visualization by harnessing the synergistic effects of a dielectric metasurface array endowed with photonic spin-decoupled capability. This approach enables the simultaneous acquisition of light-field images containing flow field information in two orthogonal dimensions, which allows for the real-time and quantitative derivation of multiple physical parameters. As a proof-of-concept, we experimentally demonstrate the applicability of the proposed visualization technique to various scenarios, including temperature field mapping, gas leak detection, visualization of various fluid physical phenomena, and 3D morphological reconstruction of transparent phase objects. This technique not only establishes an exceptional platform for advancing research in fluid physics, but also exhibits significant potential for broad applications in industrial design and vision.